ONCOLOGICAL RESULTS OF SURGICAL TREATMENT EFFECTIVENESS OF STAGE I AND II ORAL CAVITY CANCER - A. V. Karpenko; R. R. Sibgatullin; A. A. Boyko; N. S. Chumanikhina; M. G. Kostova; O. M. Nikolaeva; L. D. Roman (Опухоли головы и шеи, 2017)
Introduction. Surgical intervention is the main method of treatment of oral cavity cancer, and at early stages it»s a monomodal treatment. The study objective is to determine oncological effectiveness based on an analysis of surgical treatment of stage I and II oral cancer.Materials and methods. In the period from April 2009 to December 2014, 52 patients (37 men and 15 women) aged 39–85 (mean age was 60.2 years) with confirmed diagnosis of squamous cell carcinoma of the tongue (36 patients), the floor of the mouth (15), and the retromolar trigone (1) underwent surgery. Half of the patients were stage I, the other half – stage II. Removal of the primary tumor was accompanied by neck dissection in 35 cases (67 %). Dissection was two-sided in 8 patients. Twenty (20) modified radical dissections and 23 selective neck dissections were performed. In the majority of cases (42 patients, 80.8 %), tumors were removed transorally. Primary reconstruction was performed in 31 patients; in others, additional plastic material was used: infrahyoid flap (14 cases), submental flap (1), radial forearm flap (5), anterolateral femoral flap (1). Survival was evaluated using the Kaplan–Meier estimator incorporating patient’ dates of last visits or death. Progression-free survival took into account time to diagnosis of disease relapse in the form of local or regional recurrence. Statistical data analysis was performed using the SPSS v. 23 software.Results. Mean follow up duration was 37.4 months (1–91  months), and 27 patients (52 %) were monitored for 3 and more years, 34 (65.4 %) patients after surgery for 2 years and longer, and 46 (88.5 %) patients for more than a year. During this time, 8 patients died, and 3-year overall survival was 84.7 %. In 6 patients, disease recurrence was diagnosed, in 2 of them this event was registered twice (local recurrence in 3 cases, regional recurrence in 4 cases, locoregional recurrence in 1 case). Therefore, locoregional control was 88.5 %. Time to recurrence varied from 4 to 43 months. Three-year relapse-free survival was 91.1 %. Second primary tumors appeared 30–70  months after surgery in 4 patients: In 2 patients, they were located in the oral cavity, in 1 – in the larynx, and in 1 – in the laryngopharynx. Statistical analysis of various factors (Т stage, differentiation grade, localization, etc.) has shown that only neck dissection affected overall 3-year survival: it was 96 % in patients with neck dissection, and 64.3 % in patients without neck dissection (р = 0.012). However, these data can be explained by older age of patients who didn’t undergo neck lymph node dissection (65.2 vs. 57.6 years), and presence of a more severe concomitant pathology.Conclusion. Surgical intervention remains the main treatment method of early stage oral cavity cancer due to its high oncological effectiveness.